(untitled) (The Pakistan Development Review, 2009)
The main objective of the study is to empirically investigate the differential impact of services and manufacturing Foreign Direct Investment (FDI) on economic growth over the period of 1972 to 2008. The study further examines the role of FDI in presence of macroeconomic instability and privatisation. For the investigation of long run, Autoregressive distributed lag model (ARDL) has been used. For short run results, we used Error correction method (ECM). Our empirical results show that FDI inflow in both, service sector as well as manufacturing is contributing to economic growth positively. But it is apparent from the results that contribution of services FDI to growth is greater than that of manufacturing FDI to growth. Furthermore, the results provide coherent and sound policy recommendations for further policy adaptation regarding sectors. JEL classification: F23, F36, F43, C32 Keywords: Foreign Direct Investment, Economic Growth, Manufacturing Sector, Service Sector, Co-integration